Local controllability and optimality. (July 2021) - Avakov, E. R.; Magaril-Il'yaev, G. G.
Abstract: The concept of local controllability is introduced for a dynamical system; sufficient conditions for such controllability are presented. As a consequence, necessary conditions for a local infimum in an optimal control problem are obtained. These strengthen Pontryagin's maximum principle and extend it to more general classes of problems. Bibliography: 8 titles.